Cross-sector co-creation of a community-based physical activity program for breast cancer survivors in Colombia. (19th July 2022) - Rubio, María Alejandra; Mosquera, Daniela; Blanco, Martha; Montes, Felipe; Finck, Carolyn; Duval, Martin; Trillos, Catalina; Jaramillo, Ana María; Rosas, Lisa G; King, Abby C; Sarmiento, Olga L
Abstract: Benefits of physical activity (PA) in breast cancer survivors (BCS) are well established. However, programs to promote PA among BCS tailored to real-world contexts within low- to middle-income countries are limited. Cross-sector co-creation can be key to effective and scalable programs for BCS in these countries. This study aimed to evaluate the networking process to engage multisector stakeholders in the co-creation of a PA program for Colombian BCS called My Body . We employed a mixed-methods design including semistructured interviews, workshops and a social network analysis of centrality measures to assess stakeholders' engagement, resources and skills enabling the collaborative work, challenges, outcomes and lessons learned. The descriptive analysis and the centrality measures of the network revealed that 19 cross-sector stakeholders engaged in the My Body collaborative network. Through ongoing communication and cooperation, My Body built relationships between the academic lead institutions (local and international), and local and national public, private and academic institutions working in public health, sports and recreation, social sciences and engineering fields. The outcomes included the co-creation of the community-based PA program for BCS, its implementation through cross-sector synergies, increased relationships and communications among stakeholders, and successful dissemination of evidence and project results to the collaboration partners and other relevant stakeholders and community members. The mixed-methods assessment enabled understanding of ways to advance cross-sector co-creation of health promotion programs. The findings can help to enable continued development of sustainable cross-sector co-creation processes aimed at advancing PA promotion. Lay Summary: Collaborative work among stakeholders and researchers from different governmental sectors and disciplinary fields can be key to design and implement effective and scalable programs to promote physical activity (PA) among breast cancer survivors (BCS). This might be particularly critical in low- to middle-income countries where the implementation of evidence-based health-promoting programs tailored to real-world contexts are limited. This study aimed to evaluate the networking process to engage multisector stakeholders in the co-creation of a PA program for Colombian BCS. We employed qualitative methods and social network analyses to assess stakeholders' engagement, resources and skills enabling the collaborative work, challenges, outcomes and lessons learned. The co-creation of the program improved synergies between research, policy and practice. Communication through several channels including e-mail and workshops was the key resource to advance the collaborative work. Stakeholders underscored that cross-sector networking allowed allocating resources and achieving shared goals. Sustainable cross-sector collaborative processes are key for health promotion.